Performance-Sensitive Government Bonds - Matthias Bank; Alexander Kupfer; Rupert Sendlhofer (Credit and Capital Markets – Kredit und Kapital, 2014)
Steadily growing debt ratios indicate that current sovereign debt policy lacks important incentives for governments and politicians to fulfill it in a long-term sustainable way. To implement proper incentives, we propose the concept of performance-sensitive government bonds (PSGB) where coupon payments are closely linked to debt policy, giving strong incentives to limit debt levels and to timely restructure the economy. In addition, we show that the current mechanisms used to solve sovereign debt problems within the EMU are not only missing the right incentives but also setting the wrong ones. – – Performance-sensitive Staatsanleihen Derzeit haben Regierungen und Politiker nur wenige Anreize, die Staatsschuldenpolitik in einer langfristig nachhaltigen Weise auszuüben. Der Einsatz von performance-sensitiven Staatsanleihen, welche wir in diesem Aufsatz vorschlagen, schafft wichtige Anreize, die Verschuldung zu reduzieren und notwendige Reformen frühzeitig durchzuführen. Dieser Artikel diskutiert die Anreizwirkungen sowie die Ausgestaltung solcher Anleihen, welche sich durch Kuponzahlungen auszeichnen, die an die Schuldenpolitik des Landes gekoppelt sind. Zusätzlich wird dargelegt, dass die gegenwärtigen Instrumente zur Bewältigung der europäischen Staatsschuldenkrise zu wenige bzw. die falschen Anreize setzen.
Keywords: G12; G13; H62; H63; 330; Sovereign debt policy; government bond; incentive; contingent debt; EMU